Evaluating knowledge and capacity development in the water sector: challenges and progress. Issue 4 (19th May 2017) - Mvulirwenande, Silas; Wehn, Uta; Alaerts, Guy
ABSTRACT: As knowledge and capacity development (KCD) is increasingly acknowledged as crucial for development, the need to evaluate its impact increases, too. However, evaluating KCD in practice remains a challenge. This article aims to synthesize the current wisdom on the topic of KCD evaluation in the water sector. We discuss two leading approaches to KCD (positivist and complex adaptive systems) and their associated evaluation paradigms, the major methodological challenges facing KCD evaluation, and progress made in that respect. The article provides insights for KCD practitioners and policy makers in the water sector that can help them improve their KCD evaluation practice.